The Impact of Patient Characteristics and Antiplatelet Regimes on Clot Microstructure in Patients Treated for ST Elevation Myocardial Infarction: Clot Microstructure can Evaluate Therapeutic Efficacy - Matthew Lawrence (Clinical and Applied Thrombosis/Hemostasis, 2023)
BackgroundUnfavourable clot microstructure is associated with adverse outcomes in ST elevation myocardial infarction (STEMI). We investigated the effect of comorbidities and anti-platelet treatment on clot microstructure in STEMI patients using fractal dimension (df), a novel biomarker of clot microstructure derived from the visco-elastic properties of whole blood.MethodsPatients with STEMI (n = 187) were recruited sequentially receiving aspirin with Clopidogrel (n = 157) then Ticagrelor (n = 30). Patient characteristics and blood for rheological analysis obtained. We quantified df using sequential frequency sweep tests to obtain the phase angle of the Gel Point which is synonymous with the clot microstructure.ResultsHigher df was observed in males (1.755 ± 0.068) versus females (1.719 ± 0.061, p = .001), in patients with diabetes (1.786 ± 0.067 vs 1.743 ± 0.046, p < .001), hypertension (1.760 ± 0.065 vs 1.738 ± 0.069, p = .03) and previous MI (1.787 ± 0.073 vs 1.744 ± 0.066, p = .011) compared to without. Patients receiving Ticagrelor had lower df than those receiving Clopidogrel (1.708 ± 0.060 vs 1.755 ± 0.067, p < .001). Significant correlation with df was found with haematocrit (r = 0.331, p < .0001), low-density lipoprotein (LDL) (r = 0.155, p = .046) and fibrinogen (r = 0.182, p = .014). Following multiple regression analysis, diabetes, LDL, fibrinogen and haematocrit remained associated with higher df while treatment with Ticagrelor remained associated with lower df.ConclusionsThe biomarker df uniquely evaluates the effect of interactions between treatment and underlying disease on clot microstructure. STEMI patients with diabetes and elevated LDL had higher df, indicating denser clot. Ticagrelor resulted in a lower df than Clopidogrel signifying a less compact clot.